CURRICULUM DEVELOPMENT MANAGEMENT IN IMPROVING THE QUALITY OF ISLAMIC RELIGIOUS EDUCATION IN JUNIOR HIGH SCHOOL (SMP) MUHAMMADIYAH 3 BONTOALA - Hamzah, Nurfadhillah H.; Sumiati, Sumiati; Bakri, Muhammad Ali (Universitas Islam Negeri Alauddin Makassar, 2024)
This research examines curriculum development management in improving the quality of Islamic religious education. This research was conducted at Muhammadiyah 3 Bontoala Middle School. This research examines curriculum development in improving the quality of Islamic education at SMP Muhammadiyah 3 Bontoala. The type of research is field research, taking data sources in the field through interviews as the main source, and school data, supporting data related to curriculum development—second source. The researcher then explained several research findings regarding curriculum development in improving the quality of Islamic religious education. The results of this thesis research show that the offer for curriculum development in improving the quality of Islamic religious education at SMP Muhammadiyah 3 Bontoala is the implementation of learning through several basic learning approaches based on social juridical and pedagogical principles. The relevance of developing an Islamic education curriculum to improve the quality of Islamic education at SMP Muhammadiyah 3 Bontoala is the self-development program, counseling, and extracurricular Tadarus activities.